Development and Validation of the Spiritual Empathy Fatigue Scale (SEFC): A Psychometric Study Among Faith-Based Care Providers in Turkey - Okan, Nesrullah (Journal of religion and health, 2026)
This study aims to reveal the psychometric properties of the spiritual empathy fatigue scale (SEFC), which was developed to assess spiritual empathy fatigue (SEFC), one of the unique forms of burnout experienced by professionals providing faith-based help. SEFC is structured on four theoretical dimensions at the intersection of empathy fatigue and spiritual burnout: Empathic Overload and Overexposure, Spiritual Isolation and Loneliness, Spiritual Burnout and Faith Conflict and Questioning. In the scale development process, exploratory factor analysis (EFA) was conducted with the data obtained from the first sample (n = 301), followed by confirmatory factor analysis (CFA) on the second independent sample (n = 296). The four-factor structure obtained with Varimax rotation explains 62.97% of the total variance. CFA results show that the model fit of the four-dimensional structure of the scale is at an acceptable level (RMSEA = .065, CFI = .917, SRMR = .048). The overall internal consistency coefficient of the scale was calculated as Cronbach’s α = .926, and the α values for the sub-dimensions ranged between .857 and .894. In addition, test-retest reliability was found to be r = .831 at a 15-day interval (n = 37). Unlike the existing compassion fatigue, empathy exhaustion or religious coping scales in the literature, SEFC is the first culturally adapted scale that can assess the specific psychological burdens experienced by professionals working in spirituality-based relief services in a multidimensional manner. In this respect, the scale provides a valid and reliable assessment tool to be used in various professional practice areas, especially in disaster psychology, spiritual counselling, pastoral supervision and in-service training.